2003
DOI: 10.1007/s00213-002-1344-3
|View full text |Cite
|
Sign up to set email alerts
|

Switching patients to aripiprazole from other antipsychotic agents: a multicenter randomized study

Abstract: Any of the three strategies evaluated can be used safely for switching patients to aripiprazole from antipsychotic monotherapy. Furthermore, patients' symptoms may continue to improve after switching to aripiprazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
2
4

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(164 citation statements)
references
References 21 publications
13
145
2
4
Order By: Relevance
“…The three 6-week, medication-switch studies reported improvements in weight, BMI, and lipid profiles after therapeutic substitution of ziprasidone for olanzapine or risperidone (Weiden et al, 2003a). Short-term studies involving substitution of aripiprazole for olanzapine or risperidone also reported improvements in weight and BMI (Casey et al, 2003). However, these data did not establish whether these initial improvements could be sustained during long-term antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three 6-week, medication-switch studies reported improvements in weight, BMI, and lipid profiles after therapeutic substitution of ziprasidone for olanzapine or risperidone (Weiden et al, 2003a). Short-term studies involving substitution of aripiprazole for olanzapine or risperidone also reported improvements in weight and BMI (Casey et al, 2003). However, these data did not establish whether these initial improvements could be sustained during long-term antipsychotic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In psychiatric populations, behavioral approaches may require more intensive and costly efforts to achieve even this level of weight reduction; however, few studies have addressed these issues (Brar et al, 2005;Menza et al, 2004). Weight reduction achieved with currently approved antiobesity drugs is similarly modest over the long term (approximately 5% of initial body weight (McMahon et al, 2000)), and these drugs may be associated with adverse effects that can limit their use in psychiatric patients (eg anxiety, insomnia, or anal leakage (Casey et al, 2003)). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend was a somewhat unexpected finding, because previous studies using aripiprazole monotherapy for treatment of schizophrenia in adults resulted in a modest weight loss over an 8-week study duration (Casey et al 2003). However, more recent studies involving children have suggested that children are more likely to experience metabolic effects of aripiprazole than adults (Correll 2008).…”
mentioning
confidence: 93%
“…Nas revisões e na maioria dos estudos, os APGs demonstraram apenas poucos efeitos benéficos na cognição (Cassens et al, 1990;Sharma, 1999), e muitas variações inapropriadas de dose, combinadas com SEP ou com medicação anticolinérgica concomitante, podem ter exercido um efeito negativo na cognição. Numa metanálise que incluiu estudos comparando os efeitos dos APGs àqueles do placebo ou da não-medicação apontaram ganhos modestos a moderados nos domínios cognitivos múltiplos para os APGs (Mishara e Goldberg, 2004).…”
Section: Eficácia Dos Antipsicóticos De Primeira E Segunda Geraçõesunclassified